The Influence of the Chiller Model on Achieving and Developing Proactive Motivation Among Female Students of the Institute of Fine Arts in the Theme of Aesthetics - Ghuli, Sura Zeyad Tariq Al-qarah; Mahmoud, Mohamed Sobeih (Journal of Ecohumanism, 2024)
The research pointed to reveal the effect of the Chiller model on achieving and developing proactive motivation among female scholars of the Institute of Fine Arts in aesthetic schooling. The study depended on the experimental system. The investigation model entailed of (30) female scholars from the Institute of Fine Arts - Al-Karkh First - Department of Design, from the second year female students. The investigation means were the mental attainment assessment and the proactive motivation measure formulated by (Zayzoun 2022). The study attained the subsequent conclusions:The sample members’ cognitive achievement test mean scores show statistically significant changes in favor of the post-test at the significance level (0.05). The mean motivation scale scores of the sample members show statistically significant changes in favor of the post-test at the significant level (0.05). The effect size value was equal to (2.15), representing a large influence extent. The influence size value for the next dependent variable (motivation) was (2.75), and it also characterizes a large influence extent for the individual changeable on the contingent adjustable according to Cohen’s classification of the amount Effect size.The influence of the Chiller standard on achieving and obtaining proactive motivation amongst female scholars of the Institute of Fine Arts in aesthetic schooling.